Pengaruh Jarak Celah Bilah Penganggu Terhadap Kinerja Pompa Sentrifugal 3 Sudu - Mochammad Sarifuddin, Mochammad Arif Irfa’i, Indra Herlamba Siregar (Universitas Hasyim Asy'ari, 2021)
A device that has the basic function of moving a fluid from one container to another is called a pump. In pumps that play an important role is the impeller, now there are many modifications and innovations of pump impellers to support every industrial need. The purpose of this study was to determine the effect of differences in rotational speed variations, design variants of the impeller, and temperature variations set in such a way on the performance of centrifugal pumps. The impeller used in this study is a semi-open impeller with a total of 3 blades that uses a variable spacing of 2 mm, 3 mm, and 4 mm interfering gaps and a motor rotation of 1500 rpm, 2000 rpm, 1800 rpm, and temperature variations of 30 ° C, 40 ° C and 50 ° C. By using an electric motor as the driving force, the type of flow is radial flow, and the pipe diameter is inch. The highest head value that can be produced by this study is 15.70 meters with an electric motor speed setting of 2500 rpm. The highest capacity is 47 LPM at a rotational speed of 2500 rpm. The temperature variation achieved at 30 ̊ C was 2.3 meters and became the highest head. From the analysis of the pump with the impeller gap, the greater the blade gap on the impeller, the smaller the head, capacity, and efficiency produced by the pump.